Identification of multiple novel genetic mechanisms that regulate chilling tolerance in Arabidopsis - Sahoo, Dipak Kumar; Hegde, Chinmay; Bhattacharyya, Madan K. (Frontiers in Plant Science, 2023)
Cold stress adversely affects the growth and development of plants and limits the geographical distribution of many plant species. Accumulation of spontaneous mutations shapes the adaptation of plant species to diverse climatic conditions. Genome-wide association study of the phenotypic variation gathered by a newly designed phenomic platform with that of the single nucleotide polymorphic (SNP) loci across the genomes of 417 Arabidopsis natural variants collected from various geographical regions revealed 33 candidate genes for chilling tolerance. Investigation of at least two independent mutants for 29 of these genes identified 16 chilling tolerance genes controlling diverse genetic mechanisms. This study identified five genes encoding novel leucine-rich repeat domain-containing proteins, including three nucleotide-binding site leucine-rich repeat (NBS-LRR) proteins. Among the 16 identified chilling tolerance genes, ADS2 and ACD6 are the only two chilling tolerance genes identified earlier. The comparatively little overlap between the genes identified in this genome-wide association study of natural variants with those discovered previously through forward and reverse genetic approaches suggests that chilling tolerance is a complex physiological process governed by a large number of genetic mechanisms.